2018
DOI: 10.1093/jas/sky055
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of endophyte-infected tall fescue effects on cattle growth rates

Abstract: The objective of this study was to quantitatively summarize literature reporting endophyte-infected (Neotyphodium coenophialum) tall fescue (Festuca arundinacea) effects on cattle ADG. This meta-analysis evaluated endophyte infection level, climate, and forage yield using a literature dataset of 138 treatments from 20 articles. Three infection level measurements were tested: endophyte infection as a percentage of infected tillers (E%); ergovaline concentration in ppb ([E]); and total ergot alkaloid concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…The E+ seed contained a mixture of ergot alkaloids, with ergovaline and ergotamine being the most bioactive (Klotz, 2015b), while the E− seed contained only a trace level of ergovaline. A dietary concentration of 500 μg/kg ergovaline + ergotamine was chosen to induce toxicosis consistent with moderate environmental exposure (Liebe and White, 2018).…”
Section: Treatmentsmentioning
confidence: 99%
“…The E+ seed contained a mixture of ergot alkaloids, with ergovaline and ergotamine being the most bioactive (Klotz, 2015b), while the E− seed contained only a trace level of ergovaline. A dietary concentration of 500 μg/kg ergovaline + ergotamine was chosen to induce toxicosis consistent with moderate environmental exposure (Liebe and White, 2018).…”
Section: Treatmentsmentioning
confidence: 99%
“…BarOptima and Duramax contained low concentrations of ergovaline as well, though the concentrations were 2-to >10-fold less than those for CTE+ KY31 (Fig. Ergovaline concentrations for BarOptima and Duramax were at or below thresholds reported for cattle by Liebe and White (2018) and were below thresholds suggested for cattle in Missouri (Cornell et al, 1990). Ergovaline concentrations for Estancia, Jesup, Martin2, Texoma, and E− KY31 were nil.…”
Section: Ergovaline Analysismentioning
confidence: 85%
“…4). Liebe and White (2018) reported threshold ergovaline concentrations from 20 articles using meta-analysis; the authors concluded that cattle average daily gain decreased 33 g d −1 with each increase of 100 mg kg −1 of ergovaline concentration, and they reported a threshold ergovaline concentration of 60 mg kg −1 . 4).…”
Section: Ergovaline Analysismentioning
confidence: 99%
See 2 more Smart Citations